Assessment of Self-Perception of Transsexual Persons: Pilot Study of 15 Patients - Jasmina Barišić; Marija Milosavljević; Dragana Duišin; Borjanka Batinić; Svetlana Vujović; Srdjan Milovanović (The Scientific World Journal)
Background and Aims. There have been few studies in the area of Self-Perception in transsexual persons, except for the population of transsexual adolescents. Bearing in mind its importance not only in the assessment of personality but also in predicting adaptive capacity, the goal of our research is based on the examination of Self-Perception of adult transsexual persons. Method. The study was conducted using a Rorschach test, which provides an insight into various aspects of Self-Perception. The sample consisted of 15 transsexual persons, who passed the standard diagnostic procedure. Results. The results suggest that transsexual persons manage to maintain Adequate Self-Esteem. Hypervigilance Index and Obsessive Style Index are negative, while the values showing a negative quality of Self-Regard and the capacity for introspection tend to increase. In the process of Self-Introspection, negative and painful emotional states are often perceived. Conclusion. The estimation of Self-Perception in adult transsexual persons indicates a trend of subjective perception of a personal imperfection or inadequacy. This is probably the result of experiencing discomfort for a number of years due to gender incongruence and dysphoria, in particular in persons who enter the sex reassignment procedure later in their adulthood.